Income Analysis of Coffee Farming at Karya Manunggal Farmers Group in Bedono Village Jambu District Semarang Regency - Rosita Arum Putri Krisella; Budiraharjo, Kustopo; Handayani, Migie (JURNAL LITBANG PROVINSI JAWA TENGAH, 2023)
This research aims to analyze the income of coffee farming and analyze factors impact of land area, production output, labor contribution, fertilizer costs and experience to the income of coffee farming at Karya Manunggal Farmers Group in Bedono Village, Jambu Subdistrict, Semarang Regency. This research used case study method. Determination of the sample used proportional random sampling as many as 46 respondents at Karya Manunggal Farmers Group. The data was analyzed descriptively and quantitatively by income analyze, R/C ratio, and multiple linear regression analyze. The results showed that the income of coffee farmers at Karya Manunggal Farmers Group is Rp 1.877.509,00/year with an average land area of 5.978 m2, R/C ratio is 1,28 and considered profitable. Significant level of 0,05 showed land area, production output, labor contribution, fertilizer costs and experience simultaneously affect the income of coffee farmers, while the partial affect is land area, production output and fertilizer costs.